PENGGUNAAN MEDIA MANIPULATIF DALAM PEMPELAJARAN PENAFSIRAN DAN PEMBULATAN BILANGAN UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS IV - M, Fatimah; Asran, Mastar; Tampubolon, Budiman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract :The background of this research study mathematics problems that have not been implemented optimally , the pattern is still learning transmissive media manipulative therefore necessary to explain the concepts and procedures of mathematics at the fourth grade Elementary School 14 Engkerengas Kapuas Hulu . The purpose of this study was to describe the improvement of learning outcomes of students with manipulative media . This study used a descriptive method , the form of classroom action research . Subjects were teachers and learners . The research data in the form of scores of teachers preparing lesson plans capability , implementing learning and learning outcomes . The results of this study can concluded : the use of manipulative media in learning can improve student learning outcomes , outcome measures average score of the ability of teachers preparing lesson plans first cycle of 2.76 and 3.83 second cycle . The ability of teachers to implement the learning cycle I average score 3.96 2.91 second cycle . The average value of the first cycle of learning outcomes 59.28 , 75.35 second cycle . Data obtained from the first cycle to the second cycle increased by an average of 16.07. Keywords: Learning Mathematics, Manipulative Media, Learning Outcomes PenelitianinidilatarbelakangiadanyamasalahpembelajaranMatematika yang belumdilaksanakansecara optimal, polapembelajaranmasihbersifattransmisifkarenaituperlumedia manipulatif di kelasIV Sekolah Dasar Negeri 14 Engkerengas Kapuas Hulu. Tujuan penelitian ini untuk mendeskripsikan peningkatan hasil belajar peserta didik dengan media manipulatif. Penelitianinimenggunakanmetodedeskriptif, bentuk Penelitian Tindakan Kelas. Subjek penelitian adalah guru dan peserta didik. Data penelitian berupa skor kemampuan guru menyusun RPP, melaksanakan pembelajaran dan hasil belajar. Hasilpenelitianinidapatdisimpukan: penggunaanmedia manipulatif dalampembelajarandapatmeningkatkanhasilbelajarpesertadidik, hasiltindakan rata-rata skor kemampuan guru menyusun RPP siklusI 2,76 dan siklusII 3,8, terjadi peningkatan sebesar 1,07, Kemampuan guru melaksanakan pembelajaransiklus I rata-rata skor 2,91 siklus II 3,96, terjadi peningkatan sebesar 1,05. Rata-rata nilai hasil belajar siklus I 59,28, siklus II 75,35. Data yang diperolehdarisiklus I kesiklus II terjadipeningkatan rata-rata sebesar 16,07. Kata Kunci:Pembelajaran Matematika, Media Manipulatif, HasilBelajar